ASSESSMENT OF THE THREE R SKILLS AMONG PRIMARY SCHOOL STUDENTS - JHA, SANJEEV KUMAR (THE PRIMARY TEACHER, 2013)
The present research was an attempt to study the development of the three R Skills. For this purpose researcher developed a three R Skills test. The test was administered on the 200 students selected with systematic sampling technique from four schools. The data was analysed by using statistical techniques like mean, standard deviation and t-ratio. Research concluded that development of reading and writing skills of girls is higher than boys whereas arithmetic skill of girls and boys is equally developed. The three R skills of rural and urban students are equally developed.